2021
DOI: 10.1080/02670844.2021.1929737
|View full text |Cite
|
Sign up to set email alerts
|

Research on microstructural and property evolution in laser cladded HAZ

Abstract: In this study, the coating was fabricated on the AISI420 stainless steel substrate by laser cladding, and the 18Cr-0.2C Fe-based powder was used in the process. The substrate was close to the heat source exhibited a complex thermal cycle, as evidenced by the significant changes in microstructures and mechanical properties of those regions. The microstructure, phase compositions, mechanical and corrosion properties of the heat-affected zone (HAZ) were investigated systematically. The temperature distribution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…No heat affected zone It can be observed that microstructure is very similar in both cases (Figure 5a and 5b). The solidification features are in accordance with the literature [24][25][26][27]. A nucleation phase, characterized by small equiaxed grains, is evidenced at the interface, then a columnar growth directed mainly parallel to the <001> direction of the dendrites is observed (Figure 5a).…”
Section: Microstructure Features and Associated Chemical And Mechanic...supporting
confidence: 89%
“…No heat affected zone It can be observed that microstructure is very similar in both cases (Figure 5a and 5b). The solidification features are in accordance with the literature [24][25][26][27]. A nucleation phase, characterized by small equiaxed grains, is evidenced at the interface, then a columnar growth directed mainly parallel to the <001> direction of the dendrites is observed (Figure 5a).…”
Section: Microstructure Features and Associated Chemical And Mechanic...supporting
confidence: 89%
“…Consequently, the corrosion cannot effectively be blocked, leading to low corrosion resistance of the microdimples edges. [ 25 ] Finally, the roundness of the microdimples of the samples in the low apparent‐microcrack group changed under the action of the corrosive medium. Corrosion products were deposited inside the microdimples after corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…Also, they observed columnar and equiaxed dendritic grains in the direction of solidification. Pan et al [5] implemented 18Cr-0.2C Fe-powder on AISI420 stainless steel substrate using laser cladding method. Microstructure, phase transformations, mechanical properties, thermal cycle, corrosion properties were investigated.…”
Section: Introductionmentioning
confidence: 99%